Efficacy and safety of a quadrivalent influenza vaccine in children aged 6–35 months: A global, multiseasonal, controlled, randomized Phase III study. Issue 18 (20th April 2022) - Esposito, Susanna; Nauta, Jos; Lapini, Giulia; Montomoli, Emanuele; van de Witte, Serge
Highlights: Influenza infection was less frequent in children after QIV versus control vaccine. Efficacy against any circulating and antigenically matching strains was 54% and 68%. QIV induced antibodies against HA and NA as well as virus neutralizing antibodies. Revaccination with QIV elicited strong antibody responses for all strains. The safety and reactogenicity of QIV was comparable with control vaccine. Abstract: Background: Children are an important target group for influenza vaccination, but few studies have prospectively evaluated influenza vaccine efficacy (VE) in children under 3 years of age. This was a randomized Phase III trial to assess the efficacy, immunogenicity, and safety of an inactivated quadrivalent influenza vaccine (QIV) in young children (EudraCT: 2016–004904–74). Methods: Influenza-naïve children aged 6–35 months were randomized during three influenza seasons to receive vaccination with QIV or a non-influenza control vaccine. One group of participants was revaccinated with QIV in the subsequent influenza season. The primary efficacy endpoint was the absolute VE of QIV against influenza caused by any circulating strain. Key secondary efficacy endpoints included the absolute VE of QIV against influenza due to antigenically matching strains and immunogenicity. Safety and reactogenicity were also evaluated. Results: In total, 1005 children received QIV and 995 received control vaccine. Influenza A/B infection due to any circulating influenza strain occurred less frequently in children who received QIV versus children receiving a control vaccine. The absolute VE of QIV against any circulating influenza strain was 54% (95% confidence interval [CI]: 37%, 66%). The absolute VE of QIV against antigenically matching influenza strains was 68% (95% CI: 45%, 81%). Mean hemagglutination inhibition titers for all influenza strains in the QIV group increased post-vaccination, whereas increases were minimal in the control vaccine group; results from virus neutralization and neuraminidase-inhibition assays were generally consistent with the hemagglutination inhibition assay findings. Approximately 12 months after primary vaccination with QIV, antibody titers remained higher than pre-vaccination titers for most strains. In participants who were revaccinated, QIV elicited strong antibody responses. The overall safety profile and reactogenicity of QIV was comparable with control vaccine. Conclusion: Primary vaccination with QIV was well tolerated and effective in protecting children aged 6–35 months against influenza.